Patients with chronic periodontitis present increased risk for primary Sjögren syndrome: a nationwide population-based cohort study - Tai-Chen Lin (PeerJ, 2018)
Many reports have mentioned the association between chronic periodontitis (CP) and primary Sjögren syndrome (pSS). However, no cohort study has been performed for the risk of pSS in patients with CP. In this study, we evaluated the risk of pSS from CP exposure in a nationwide population-based cohort study in Taiwan. We studied the claims data of Taiwanese population from 2001 to 2012. We identified 76,765 patients with CP from the National Health Insurance Database in Taiwan. We also selected 76,765 controls that were randomly frequency matched by age, sex, and index year from the general population. We analyzed the risk of pSS by using Cox proportional hazards regression models including sex, age, and comorbidities. In this study, 76,765 patients with CP (mean age: 40.8 years) and 76,765 controls (mean age: 41.0 years) were followed-up for 8.54 and 8.49 years, respectively. A total of 869 cases of pSS were identified in CP cohort and 483 cases in non-CP cohort. Multivariate Cox regression analysis indicated that the incidence rate of pSS was significantly higher in CP cohort than those who in non-CP cohort (adjusted HR: 1.79, 95% CI [1.60–2.00]). Taken together, this nationwide retrospective cohort study demonstrated that the risk of pSS was significantly higher in patients with CP than in the general population. The association between CP and pSS was significant in the female group.